Optimasi Pendistribusian Produk AQUA dengan Menggunakan Metode Least Cost dan Modifed Distribution (Studi Kasus di PT Tirta Sibayakindo) - Sembiring, Bani; Mansyur, Abil (Universitas Negeri Medan, 2018)
This study aims to construct an initial consideration for decision maker to minimize the distribution costs at PT. Tirta Sibayakindo, a soft drink producer andÂ distributor in Indonesia. Least Cost methods was used to gain an initial solution and Modified Distribution methods was used to gain the final solution for this transportation problem. Data was analyzed using the Least Cost methods. Results showed that the distribution cost was Rp165.535.000,- when ordinary calculation was implemented. When Least Cost method was used, the distribution cost was Rp100.200.000,-, so the soft drink company can save the distribution cost of Rp65.335.000,-. From this results, we suggest the company to implement the transportation algorithm when they dealed with distribution cost optimization.